Evaluating the Impact of Glycemic Control, Lipid Derangement and Antioxidant Status on Progression of Diabetic Retinopathy - Kiran, P. Usha; Rao, B. Srinivasa (Achievements and Challenges of Medicine and Medical Science Vol. 8, 2024)
Background: Diabetes Mellitus is a global health problem. It is a potentially life-threatening metabolic syndrome. There were nearly 171 million diabetics worldwide in 2000 with the number projected to be almost 2.5 times, about 366 million by the year 2030 (prevalence rate of 4.4%) with the greatest number of cases expected in China and India. Patients with diabetes show a difference in serum uric acid pattern in relation to the duration of the disease along with glycemic status, lipid derangements and complications associated with the disease. Aims and Objectives: To study HbA1c levels to know the blood sugar levels for the past 3 months to assess the glycemic control and to estimate lipid profile to assess the risk of microvascular complications like Retinopathy in diabetic cases. Serum uric acid levels are estimated to evaluate its role in the pathophysiology of diabetes and to establish its association with glycemic control and lipid profile which helps to understand the onset and progression of complications such as retinopathy. Materials and Methods: The present study consists of 75 cases of chronic diabetes with retinopathy as a complication in the age group of 45-75 years. The values of HbA1c, lipid profile and uric acid in cases are compared with that of 50 apparently healthy non-diabetics who are of the same age group. All the subjects were from the ophthalmology department of Govt. General Hospital, Kakinada and also from Nayana Eye Care Hospital, Kakinada. Results: The Mean Values of HbA1C and lipid profile were significantly high in diabetic retinopathy cases (p<0.0001) as compared to the control group. The Mean values of uric acid in diabetic retinopathy cases do not show a significant difference from that of the control group (p=0.446). Conclusion: The study shows that poor glycemic control plays a major role in the onset and progression of diabetic retinopathy. The significant changes in the lipid profile levels in diabetic retinopathy indicate lipid peroxidation plays a key role in the progression of the disease. Serum uric acid level has not shown statistically significant changes in diabetic retinopathy implying no role of uric acid in the progression of disease.